Pendampingan Karang Taruna untuk Penguatan Jiwa Kewirausahaan Berbasis Potensi Lokal di Desa Kedungturi Taman Sidoarjo - Sutono Sutono; Achmad Khusnan Arif (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Karang Taruna is a youth organization that plays a strategic role in developing the social and economic capacity of rural communities. However, local potential is often underutilized due to limited entrepreneurial knowledge, managerial skills, and access to mentoring. This community service program aimed to assist the Karang Taruna of Kedungturi Village, Taman Subdistrict, Sidoarjo, in fostering an entrepreneurial spirit based on the village’s local resources. The implementation method applied a participatory approach that directly involved youth through several stages: village potential mapping, entrepreneurship training, business mentoring, and facilitation of digital marketing access. The mentoring process provided not only theoretical knowledge but also practical experience in developing business ideas that correspond to local resource characteristics.The results of the program indicated an increased understanding among Karang Taruna members regarding entrepreneurship concepts, business management strategies, and the use of digital technology. Furthermore, the program successfully initiated three new business ventures based on local potential, namely traditional culinary products, waste-based handicrafts, and digital services. The establishment of a youth entrepreneurship team under Karang Taruna further strengthened collective commitment to developing the village’s creative economy. The impacts were not limited to improved skills but also included the growing awareness of the importance of local resource–based economic independence.In conclusion, this program demonstrates that participatory mentoring through Karang Taruna can serve as an effective strategy to strengthen the entrepreneurial spirit of rural youth while promoting local economic independence and sustainability.